Edukasi IMD terhadap Pemberian ASI Eksklusif di Puskesmas Mapilli Kecamatan Mapilli Kabupaten Polewali Mandar - Hamdan Nur; Arlin Adam; Andi Alim; Ashriady Ashriady (Jurnal Kesehatan Manarang, 2019)
The impact of not fulfilling exclusive breastfeeding in the first 6 months of a baby's life is the risk of malnutrition. Coverage of exclusive breastfeeding in Polewali Mandar is still low so there needs to be an increase in early breastfeeding initiation. This study aims to analyze the effect of Early Breastfeeding Initiation education on the provision of exclusive breastfeeding at the Mapilli Health Center in Mapilli District, Polewali Mandar Regency. This research is an analytical study with a cross-sectional design with a total sample of 86 people. Data collection was carried out by interviewing, observing, and documenting with data analysis techniques using SPSS 16 software. Results This study concluded (1) the influence of Early Initiation Early Education on exclusive breastfeeding (2) the absence of influence of family support for exclusive breastfeeding presence and absence of family support The mother continues to provide breastfeeding for her child (3) the absence of influence of the mother's work status on providing exclusive breastfeeding because the mother works or does not, the mother continues to breastfeed her child (4) from the Early Breastfeeding Initiation education, family support and work towards exclusive breastfeeding is only one that greatly influences the success of breastfeeding mothers, namely Early Breastfeeding Initiation education. This study suggests further research needs to be done by using better research designs such as prospective cohorts and larger sample sizes to reduce recall bias and be able to control for confounding factors and consider aspects of determinants of breastfeeding determination.